'Nois por nois': movimentos sociais de comunicação em São Paulo - Valiengo, Caio Becsi (2016)
This research seeks to analyze the social movements located in the field of communication in São Paulo, especially those organizations and groups that work directly in the production of media content. The groups studied here are composed primarily of young people, residents of the outskirts of São Paulo, whose purpose is to engage in symbolic disputes through an alternative journalistic production in the construction of the collective imagination. These are groups who make a counterpoint to the mainstream media through the construction of alternative and counter-hegemonic narratives, historically made invisible by traditional media outlets. They represent projects that aim radical changes in society and the empowerment and leadership of young people and young residents of the periphery, of black people, and the subaltern classes whose voices are silenced